Assessment of Paratuberculosis international official reporting in Europe using the information supplied to the WOAH by National Veterinary Services - Angela Fanelli; Michela Galgano; Alessio Sposato; Domenico Buonavoglia (Veterinaria Italiana, 2022)
The present study characterizes the epidemiological situation of Paratuberculosis (PTB) in Europe during the last 24 years, using the information officially reported to the World Organisation for Animal Health (WOAH) by the National Veterinary Services (NVS) of the European countries. The prevalence of PTB at country level was described during the study period. A Cox proportional hazards (PH) regression analysis was implemented to evaluate the reporting behaviour. The most affected countries were found in southern and western Europe, whereas PTB presence was lower in northern and eastern Europe. PTB was routinely declared as a notifiable disease in 65% of the countries. Less than 50% of the countries routinely implemented passive surveillance, and only 19%, reported active surveillance for disease detection. Results of the Cox PH regression indicate that the Gross National Income (GNI) per capita and the application of active surveillance significantly influence the recurrence of PTB reporting. In countries with lower and upper middle income, the hazard of recurrence is 0.13 and 0.18 times lower than in countries with high income. The hazard of recurrence in countries that infrequently and moderately applied active surveillance is 1.99 and 1.65 times higher than in countries that routinely applied active surveillance. Findings of this work highlight an important variation in the reporting behaviour, disease status and surveillance across Europe.